Land, Slave Labor and Law: Engaging Ancient Israel's Economy - Glass, Zipporah G. (Journal for the study of the Old Testament, 2000)
Engaging ancient Israel's economy is important for explicating economic processes in the social and legal composition of the society. Using biblical and extra-biblical texts, archaeological data, and knowledge primarily from the fields of anthropology and economic sociology, scholars have sharply delineated the processes of latifundialization when constructing representations of societal structure and agricultural economy in the ancient world. The purpose of this paper is to be in dialogue with this scholarship, yet move to a level of systemic analysis that treats the pertinence of three factors—land, slave labor and law. In this context, the economy of land and labor is used as an alternative optic for viewing and understanding the manumission laws of Deuteronomy 15.